The Effect of the Brain-based Learning Strategy on Developing Critical Thinking Among Students of the First Grades Teacher’s Department in the Educational Research Curriculum Subject (Journal of Misan Researches, 2023)
The study aimed to identify the effect of the brain-based learning strategy on developing critical thinking among students of the first grades teacher department in the educational research curriculum subject. The sample consisted of (90) male and female students, the experimental group included (45) male and female students, and the control group (45) ) Male and females as well, the researcher adopted the Critical Thinking Scale (Al-Saadi, 2010) as a tool for his research and treated the data statistically using the statistical bag (spss) and used the t-test for two independent samples, the Pearson correlation coefficien,t and the Spearman equation, and the study concluded that there are statistically significant differences at the level of Significance (0.05) between the average scores of the experimental group and the average scores of the control group in the critical thinking scale. The researcher presented a set of recommendations and suggestions in light of the study results.